Changes in running economy during a 5-km run in trained men and women - Thomas, D. Q.; Fernhall, B.; Granat, H. (The Journal of Strength and Conditioning Research, 1999)
Research indicates that running economy (RE) changes during a 5-km run. However, the mechanisms accounting for this variation have not been identified. This study explored the effects of a 5-km run on the RE, minute ventilation (VE), blood lactate (LA), and core temperature (CT) of 40 distance runners (21 men and 19 women). After an initial testing session to determine maximum oxygen consumption (o2max), each subject (age: 30.8 years, range: 21-48 years; o2max: 54.9 ml·kg1·min1, SD ± 6.9) performed a 5-km run on a treadmill at a constant pace selected to elicit an intensity equivalent to 80-85% of their o2max. The data provide response characteristics for an early run phase (P1, 5 minutes into the run) and an end-of-the-run phase (P2, during the last minute of the run). Oxygen consumption was used to determine RE. Heart rate (HR), VE, LA, and CT were measured during both phases. All variables increased significantly between P1 and P2 (p < 0.01), and the increases were similar for men and women. During the 5-km run, changes in RE and VE were significantly related (r = 0.64; p < 0.05). When the data were analyzed by sex, stronger correlations were found for the women for RE and VE (r = 0.80; p < 0.05) compared with men (r = 0.59; p < 0.05). The changes in RE and LA (r = 0.45; p < 0.05) and LA and VE (r = 0.61; p < 0.05) were significantly related only in the women runners, whereas the men runners did not demonstrate these relationships. The combined contributions of changes in VE, LA, CT, and sex were evaluated through stepwise regression. The multiple regression, using all subjects, showed that only the change in VE was included as an independent variable (p < 0.05). None of the other variables contributed significantly to the change in o2. Conducting the same multiple regression on the men and women separately produced the same results for both groups, i.e., only the change in VE was included as an independent variable, and none of the other changes contributed significantly to the change in o2.